Monetary Policy and Multiple Equilibria - Jess Benhabib; Stephanie Schmitt-Grohe; Martin Uribe (Rutgers University, Department of Economics, 1999)
In this paper, we characterize conditions under which interest rate feedback rules that set the nominal interest rate as an increasing function of the inflation rate induce aggregate instability by generating multiple equilibria. We show that these conditions depend not only on the monetary-fiscal regime (as emphasized in the fiscal theory of the price level) but also on the way in which money is assumed to enter preferences and technology. We provide a number of examples in which, contrary to what is commonly believed, active monetary policy in combination with a fiscal policy that preserves government solvency under all circumstances gives rise to multiple equilibria, and passive monetary policy renders the equilibrium unique. Our general conclusion holds in flexible- and sticky-price environments as well as under backward- or forward-looking interest rate feedback rules.
Keywords: E31; E52; E63; 330; Interest rate feedback rules; multiple equilibria; sticky prices